Institutional Approaches to Divorce Prevention: A Comparative Study of Premarital Counseling in Indonesia, Malaysia, and Thailand - Nur Syafiqoh; Muhammad Fikri Ramadhan; Abdulloh Sama-ae (Jurnal Hukum Keluarga, 2026)
The increasing rate of divorce in Muslim societies has raised concerns about the effectiveness of preventive mechanisms designed to strengthen family resilience. One of the strategies widely promoted in Islamic family law is premarital counseling, which aims to prepare prospective couples with knowledge and skills necessary for building a stable marriage. This study aims to analyze the role of premarital counseling in preventing divorce through a comparative examination of Indonesia, Malaysia, and Thailand. The research employs a qualitative approach using comparative legal analysis combined with a socio-legal perspective. Data were obtained from primary sources, including reports and institutional practices related to premarital counseling in Indonesia, particularly through the Marriage Development and Preservation Advisory Body (BP4) and the Office of Religious Affairs (KUA) in Deli Serdang Regency, as well as secondary sources such as legal documents, academic literature, and policy reports concerning Islamic family law in the three countries. The findings reveal that each country adopts a different institutional approach to premarital counseling. Malaysia implements the most formalized system through mandatory premarital courses integrated into marriage registration under the supervision of religious authorities. Indonesia adopts a semi-institutionalized model where counseling programs are facilitated by BP4 and KUA but are not always strictly mandatory. Meanwhile, Thailand relies primarily on community-based religious initiatives due to the limited formal recognition of Islamic family law within the national legal framework. The comparative analysis indicates that stronger institutional regulation and standardized counseling programs contribute to more effective divorce prevention mechanisms. Strengthening premarital counseling policies and institutional coordination may therefore enhance family resilience and reduce divorce rates in Muslim societies